منهجية التركيز على متعلم اللغة الإنكليزية في الجامعات السورية (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This article addresses the question of the feasibility  of a learner- centered approach to EFL at Syrian Universities . It also investigates the knots that are likely to hinder the application of such a model in a Syrian context .   The solution offered to eliminate such obstacles is seen through “ Learner Training ”  programs, which equip the learners with the ability to “ learn how to learn ” and to utilize their self directive efforts in the best way, i.e. to be autonomous learners who manage to have control over their learning  process outside the confines of the classroom   تتناول هذه المقالة مسألة الملائمة في تطبيق منهجية التركيز على متعلم اللغة الإنكليزية في الجامعات السورية وتبحث في الإشكالات التي قد يواجهها تطبيق منهج كهذا ضمن سياق سوري . تعرض المقالة حلاً قد يزيل هذه الصعوبات وهو في تطبيق برامج " تدريب المتعلم " الذي يزوده بالقدرة على " التعلم كيف يتعلم " والإستفادة من جهوده الذاتية بالطريقة المثلى ، أي بجعله متعلما مستقلا يمكنه السيطرة على العملية التعليمية خارج حدود الصف .